2020
DOI: 10.1007/s13197-020-04607-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of starter culture inoculation on microbial community diversity and food safety of Chinese Cantonese sausages by high-throughput sequencing

Abstract: Effects of starter culture composed of Lactobacillus sakei, Pediococcus pentosaceus, Staphylococcus xylosus and Staphylococcus carnosus at the ratios (w/w) of 1:1:1:1 on bacterial community diversity and food safety of Chinese Cantonese sausages were demonstrated by highthroughput sequencing technology. At genus level, spoilage organisms and pathogenic bacteria such as Vibrio spp., Acinetobacter spp., Enterobacter spp., Yersinia spp. accounted for 54.13%, 10.01%, 6.94% and 5.35% of bacterial in the initial fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
3
21
1
Order By: Relevance
“…The TVBN values in beef samples during storage at 4 °C are given in Figure 1b. The initial TVB-N values were 7.18 mg/100 g, 6.55 mg/100 g and 7.53 mg/100 g in Group C, Group SL and Group NA, respectively, which were all lower than 10 mg/100 g and indicative of good meat quality (Wang et al, 2021;Tian et al, 2017). However, a significant (p < 0.05) different increase patterns of TVB-N contents was presented in control and preservative treatment along with storage.…”
Section: Comparative Effects On Physicochemical Characteristics Of Chilled Beef During Storagementioning
confidence: 83%
“…The TVBN values in beef samples during storage at 4 °C are given in Figure 1b. The initial TVB-N values were 7.18 mg/100 g, 6.55 mg/100 g and 7.53 mg/100 g in Group C, Group SL and Group NA, respectively, which were all lower than 10 mg/100 g and indicative of good meat quality (Wang et al, 2021;Tian et al, 2017). However, a significant (p < 0.05) different increase patterns of TVB-N contents was presented in control and preservative treatment along with storage.…”
Section: Comparative Effects On Physicochemical Characteristics Of Chilled Beef During Storagementioning
confidence: 83%
“…Likewise, Cheng et al [90] obtained a 43% reduction of residual nitrite content due to the inoculation of Lactiplantibacillus plantarum GIM 1.191, Pediococcus pentosaceus GIM 1.428, and Debaryomyces hansenii GIM 2.184 in the production of Chinese Cantonese sausage. Wang et al [91] reported a similar effect in the production of Chinese Cantonese sausage with a multi-species starter culture (Lactobacillus sakei, Pediococcus pentosaceus, Staphylococcus xylosus, and Staphylococcus carnosus) in relation to non-inoculated sausage.…”
Section: Residual Nitrite and Nitrosamine Accumulation And Microbial ...mentioning
confidence: 80%
“…These authors indicated significant reduction in the formation of total nitrosamine content as well as in N-nitrosodimethylamine, N-nitrosodiethylamine, and N-nitrosopyrrolidine during processing. One of the possible explanations for the effect of starter culture in the residual nitrite content and formation of nitrosamines is the pH drop and limiting the availability of precursors (nitrite and amines) [91,92]. However, it seems that other factors may affect the relation between the use of starter cultures and residual nitrite content due to the significant differences in pH and a w along with a non-significant difference in the residual nitrite content between inoculated (Lactiplantibacillus plantarum GM77 and Staphylococcus xylosus GM92) and non-inoculated fermented and cooked sucuk sausages [93].…”
Section: Residual Nitrite and Nitrosamine Accumulation And Microbial ...mentioning
confidence: 99%
“…The initial TVB-N level was 7.25 mg/100 g and 7.47 mg/100 g in Group C and Group SL, respectively, suggesting a good meat quality (Wang et al, 2021;Tian et al, 2017). Subsequently, the TVB-N level in Group C increased and reached the rejection level on the 3 rd day.…”
Section: Quality Traits Of Chilled Samplesmentioning
confidence: 91%